2002
DOI: 10.3354/cr022245
|View full text |Cite
|
Sign up to set email alerts
|

Variations of erythemal ultraviolet irradiance and dose at Tartu/Tõravere, Estonia

Abstract: The variations of erythemally weighted ultraviolet (UV) irradiance and its relationships with atmospheric characteristics during 3 annual cycles (1998)(1999)(2000) at 1 site (Tõravere, Estonia; 58.3°N, 26.5°E; 70 m above sea level) were studied, with the further aim to estimate the erythemal doses for past years. In clear sky conditions the daily erythemal dose and noon irradiance exhibit total-ozone-related asymmetry in the annual cycle, with 27% lower values at spring equinox than at autumnal equinox. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…3. Similar result was found by [8] which states that the variation of solar UV Index in Estonia for March 29 (2000), September 13 (1998) and September 8 (1999) are 2.51, 3.60 and 3.58 respectively. Data analysis showed that, clouds sometimes enhanced the solar UV radiation while in other cases it reduced the solar UV radiation reaching the earth's surface.…”
Section: Resultssupporting
confidence: 84%
“…3. Similar result was found by [8] which states that the variation of solar UV Index in Estonia for March 29 (2000), September 13 (1998) and September 8 (1999) are 2.51, 3.60 and 3.58 respectively. Data analysis showed that, clouds sometimes enhanced the solar UV radiation while in other cases it reduced the solar UV radiation reaching the earth's surface.…”
Section: Resultssupporting
confidence: 84%
“…However, in some recent studies the groundbased/satellite measurements and model simulations have been used to identify changes in the surface UV and processes responsible for the UV radiation changes (e.g. McElroy, 1993, Borderwijk et al, 1995;Zerefos et al, 1995;Krzyścin, 1996;Weatherhead et al, 1997;Udelhofen et al, 1999;den Outer et al, 2000;Kaurola et al, 2000;Matthijsen et al, 2000;Eerme et al, 2002). These studies confirm that the UV changes are driven by various factors: ozone, cloudiness, aerosols, and surface albedo.…”
Section: Introductionmentioning
confidence: 84%
“…In our previous reconstructions only the period from the vernal equinox to the autumnal equinox was treated (Eerme et al, 2002b(Eerme et al, , 2003 and also a smaller data set of measured erythemal doses was used for deriving the statistical relationships between the daily erythemal dose and its proxies.…”
Section: Methodsmentioning
confidence: 99%
“…The reconstructions of erythemal doses based on proxy data and radiative transfer calculations have recently been made by several authors (Kaurola et al, 2000;Ziemke et al, 2000;Fioletov et al, 2001;Eerme et al, 2002b;Lindfors et al, 2003;Fioletov et al, 2004;Kryścin et al, 2004;Lindfors and Vuilleumier, 2005;den Outer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%